2017
DOI: 10.1111/1477-9552.12210
|View full text |Cite
|
Sign up to set email alerts
|

Public Preferences and Willingness to Pay for Forest Disease Control in the UK

Abstract: Invasive pests and diseases in trees impose a range of costs on society related to reductions in timber values, impacts on recreational opportunities and effects on forest biodiversity. These costs need to be considered when assessing control options and developing public policy. We investigate the preferences and willingness to pay of the UK general public for a range of forest disease control measures using a choice experiment with a sample of 605 people. Respondents were relatively well informed about gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Similarly, in a study on marine ecology conservation in Western Australia, Rogers (2013b) found that utility for the same conservation outcomes differed depending on the management process specified: respondents typically preferred processes that were less restrictive in terms of human use of the marine reserve. More recently, Sheremet et al (2017) also concluded that public support (for forest disease control) is conditional on the type of control measures used. On the other hand, Hanley et al (2010) found that respondents were largely indifferent to how conservation objectives (for raptors in Scottish moorlands) were achieved, implying that the benefits are roughly equal across management alternatives if the same level of environmental protection is achieved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in a study on marine ecology conservation in Western Australia, Rogers (2013b) found that utility for the same conservation outcomes differed depending on the management process specified: respondents typically preferred processes that were less restrictive in terms of human use of the marine reserve. More recently, Sheremet et al (2017) also concluded that public support (for forest disease control) is conditional on the type of control measures used. On the other hand, Hanley et al (2010) found that respondents were largely indifferent to how conservation objectives (for raptors in Scottish moorlands) were achieved, implying that the benefits are roughly equal across management alternatives if the same level of environmental protection is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…There are some studies that estimate households' willingness to pay (WTP) for the management of other invasive species in other parts of the world. For example, Florida residents' WTP to control invasive plants in state Parks (Adams et al, 2011); French households' WTP to reduce nuisance from invasive Asian ladybirds (Chakir et al, 2016); and UK households' WTP for tree disease control programs in UK forests (Sheremet et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This attention often focuses on the potential impacts of the outbreaks, especially in terms of effects on biodiversity and landscape, and the effectiveness of the government in preventing new incursions or managing pests and diseases already established. As Sheremet et al (2017) indicate, when public funds are used for disease and pest control programmes, it is important to consider public attitudes towards trees and woodlands and their preferences for mitigation efforts. However, currently there is little empirical evidence for policy makers to refer to in order to characterise the nature of public attentiveness to tree pest and disease outbreaks, nor how publics might respond to evolving outbreaks and management actions (Flint 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Alongside considering how public opinion affects management and policy-making, such as a lack of support for chemical pest control or clear-felling as control measures (Sheremet et al 2017), understanding how lay publics interpret and respond to risk events is important for risk communication. Raising awareness without triggering undue alarm (Timotijevic and Barnett 2006) may require tailoring notifications and information about risk to particular circumstances, interests and knowledge of a heterogeneous set of lay publics (Quine et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, such studies are predominantly associated with large-scale national surveys which identify moderate levels of public concern about tree pests and diseases, particularly in terms of impacts on woodlands and ecosystem services, but very low levels of awareness [33,34]. Other studies on the social acceptability of eradication and control measures provide a public mandate for management of outbreaks rather than a 'do nothing' course of action [35][36][37]. Such studies provide useful general indicators about the public mood and preferences for action, but their use of aggregated survey data provides little insight into the individual underlying subjective values and beliefs that influence the perceptions of respondents.…”
Section: Introductionmentioning
confidence: 99%